Research and Development and Intra-industry Spillovers: An Empirical Application of Dynamic Duality - Bernstein, Jeffrey I.; Nadiri, M. Ishaq (Review of Economic Studies, 1989)
The authors estimate a model of production and investment based on the theory of dynamic duality. They are particularly interested in the effects of R&D spillovers and in calculating the social and private rates of return. Cost-reducing, factor-biasing and capital-adjustment spillover effects are estimated for four industries. The existence of R&D spillovers implies that the social and private rates of return to R&D capital differ. The authors estimate that the social return exceeds the private return in each industry. Moreover, there is significant variation across industries in the differential between the social and private rates of return. Copyright 1989 by The Review of Economic Studies Limited.